Meta-Analysis of the Effect of Chest Shielding on Preventing Patent Ductus Arteriosus in Premature Infants - Mannan, Javed; Amin, Sanjiv B. (American Journal of Perinatology, 2017)
Objective This study aims to perform a meta-analysis of randomized studies to evaluate if chest shielding during phototherapy is associated with decreased incidence of patent ductus arteriosus (PDA) in premature infants.Design/Methods We used published guidelines for the meta-analysis of clinical trials. The search strategy included electronic searches of CINAHL, CENTRAL Cochrane Library, MEDLINE, PubMed, and abstracts presented at the Pediatric Academic Societies. Inclusion criteria were randomized controlled trials (RCTs), quasi-RCTs or cluster RCTs published in English and involving chest shielding during phototherapy in premature infants with PDA as an outcome. Exclusion criteria involved case reports, case series, and multiple publications from the same author. Heterogeneity testing using Q statistics was performed to evaluate the variance between studies.Results Two RCTs met study criteria. There was heterogeneity (I2: 55.4%) between the two trials. Meta-analysis of RCTs using the random effect model demonstrated that chest shielding during phototherapy was associated with decreased incidence of PDA (odds ratio: 0.47, 95% confidence interval: 0.23–0.96). There was no publication bias on Eggers test. Heterogeneity was seen in gestational age, gender, prophylactic use of postnatal indomethacin, duration of phototherapy, and assessment of PDA.Conclusion Chest shielding during phototherapy may be associated with decreased incidence of PDA among premature infants.
Keywords: chest shielding; patent ductus arteriosus; hyperbilirubinemia; phototherapy